APPLICATION OF THE WEIGHTED PRODUCT METHOD FOR DETERMINING ASSISTANCE OF JOINT BUSINESS GROUP - Wahyuni, Sri; Siregar, Iqbal Kamil; Sudarmin, Sudarmin (JURTEKSI (jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: Asahan District Social Service is one of the government agencies in Asahan District. This agency is tasked with serving the community and providing the best information for the community, especially in terms of data processing. One of the government programs used to tackle poverty is KUBE. In general, the problems that occur in KUBE are still not optimal and not on target, so that sometimes many residents protest because residents who should receive assistance do not receive assistance and conversely residents who should not have the right to receive assistance from the Joint Business Group (KUBE). By knowing the deficiencies found in the manual calculations carried out by the Asahan District Social Service. So that beneficiaries can be determined according to the criteria determined by the Asahan District Social Service. Then a system was created using the Weighted Product method to carry out accurate calculations in providing assistance made with the PHP programming language with MySQL Database, to create a new computerized decision support which is a good alternative by prioritizing effectiveness and efficiency in determining the provision of assistance to Joint Business Groups (Joint Business Groups). KUBE). The purpose of designing a Joint Business Group assistance decision system can assist Asahan Regency social service employees in determining the granting of Joint Business Groups (KUBE).            Keywords: decision support system; KUBE; weighted product (WP) Abstrak: Dinas Sosial Kabupaten Asahan merupakan salah satu instansi pemerintah yang ada di Kabupaten Asahan. Badan ini bertugas untuk melayani masyarakat dan memberikan informasi terbaik bagi masyarakat terutama dalam hal pengolahan data. Salah satu program pemerintah yang digunakan untuk menanggulangi kemiskinan adalah KUBE. Secara umum permasalahan yang terjadi di KUBE masih belum optimal dan belum tepat sasaran, sehingga terkadang banyak warga yang protes karena warga yang seharusnya menerima bantuan tidak mendapatkan bantuan dan sebaliknya warga yang seharusnya tidak berhak mendapatkan bantuan dari Kelompok Usaha Bersama (KUBE). Dengan mengetahui kekurangan yang terdapat pada perhitungan manual yang dilakukan oleh Dinas Sosial Kabupaten Asahan. Sehingga dapat ditentukan penerima manfaat sesuai dengan kriteria yang ditentukan oleh Dinas Sosial Kabupaten Asahan. Tujuan dibuat sistem dengan menggunakan metode Weighted Product untuk melakukan perhitungan yang akurat dalam pemberian bantuan yang dibuat dengan bahasa pemograman  PHP dengan Database MySQL, untuk membuat pendukung keputusan terkomputerisasi baru yang merupakan alternatif yang baik dengan mengutamakan efektifitas dan efisiensi dalam penentuan pemberian bantuan Kelompok Usaha Bersama (KUBE). Maka perancangan sistem keputusan bantuan Kelompok Usaha Bersama dapat membantu pegawai dinas sosial Kabupaten Asahan dalam menentukan pemberian Kelompok Usaha Bersama (KUBE). Kata kunci: KUBE; sistem pendukung keputusan; weighted product (WP)